Keep It Moving?: Conserving Kinetic Art - Rachel Rivenc (Getty Publications, 2018)
Kinetic art not only includes movement but often depends on it to produce an intended effect and therefore fully realize its nature as art. It can take a multiplicity of forms and include a wide range of motion, from motorized and electrically driven movement to motion as the result of wind, light, or other sources of energy. Kinetic art emerged throughout the twentieth century and had its major developments in the 1950s and 1960s.